Positive effects of voluntary running on metabolic syndrome-related disorders in non-obese hereditary hypertriacylglycerolemic rats - Škop, Vojt ch; Malínská, Hana; Trnovská, Jaroslava; Hüttl, Martina; Cahová, Monika; Blachnio-Zabielska, Agnieszka; Baranowski, Marcin; Burian, Martin; Oliyarnyk, Olena; Kazdová, Ludmila (PloS one, 2015)
While metabolic syndrome is often associated with obesity, 25% of humans suffering from it are not obese and the effect of physical activity remains unclear in such cases. Therefore, we used hereditary hypertriaclyglycerolemic (HHTg) rats as a unique model for studying the effect of spontaneous physical activity [voluntary running (VR)] on metabolic syndrome-related disorders, such as dyslipidemia, in non-obese subjects. Adult HHTg males were fed standard (CD) or high-sucrose (HSD) diets ad libitum for four weeks. Within both dietary groups, some of the rats had free access to a running wheel (CD+VR, HSD+VR), whereas the controls (CD, HSD) had no possibility of extra physical activity. At the end of the four weeks, we measured the effects of VR on various metabolic syndrome-associated parameters: (i) biochemical parameters, (ii) the content and composition of triacylglycerols (TAG), diacylglycerols (DAG), ceramides and membrane phospholipids, and (iii) substrate utilization in brown adipose tissue. In both dietary groups, VR led to various positive effects: reduced epididymal and perirenal fat depots; increased epididymal adipose tissue lipolysis; decreased amounts of serum TAG, non-esterified fatty acids and insulin; a higher insulin sensitivity index. While tissue ceramide content was not affected, decreased TAG accumulation resulted in reduced and modified liver, heart and skeletal muscle DAG. VR also had a beneficial effect on muscle membrane phospholipid composition. In addition, compared with the CD group, the CD+VR rats exhibited increased fatty acid oxidation and protein content in brown adipose tissue. Our results confirm that physical activity in a non-obese model of severe dyslipidemia has many beneficial effects and can even counteract the negative effects of sucrose consumption. Furthermore, they suggest that the mechanism by which these effects are modulated involves a combination of several positive changes in lipid metabolism.
Keywords: Rats; zvířata; fosfolipidy; bílá tuková tkáň; Cell Membrane; ceramidy; mužské pohlaví; metabolický syndrom; hnědá tuková tkáň; buněčná membrána; Phospholipids; Lipid Metabolism; Metabolic Syndrome; Running; Triglycerides; hypertriglyceridemie; kosterní svaly; Muscle, Skeletal; triglyceridy; Adipose Tissue, Brown; Ceramides; běh; Adipose Tissue, White; Animals; oxidační stres; svalové buňky; metabolismus lipidů; Male; Muscle Cells; Oxidative Stress; krysa rodu Rattus; Hypertriglyceridemia